Developing Texting for Relapse Prevention: A Scalable mHealth Program for People With Schizophrenia and Schizoaffective Disorder. Issue 10 (October 2019) - Ybarra, Michele L.; Rodriguez, Katrina; Madison, Hannah; Mojtabai, Ramin; Cullen, Bernadette A.
Abstract : Abstract: Symptom relapse in people with schizophrenia and schizoaffective disorder is common and has a negative impact on the course of illness. Here, we describe the development of Texting for Relapse Prevention, a scalable, cost-effective text messaging relapse prevention program that queries patients' "early warning signs" daily. Results of development focus groups and content advisory teams with 25 patients and 19 providers suggest that patients were enthusiastic about the program and thought that receiving daily messages about their symptoms would help them feel supported. Providers also were positive about the idea but worried that the program might interfere with patient-provider communication if patients thought that the messages were coming from providers. Patients found the content positive and actionable. The program was improved to address this feedback. This iterative development process that included multiple stakeholders ensured that the program is feasible and acceptable to both patients and providers. Abstract : Supplemental digital content is available in the text.